PENGARUH PENGGUNAAN APLIKASI KECERDASAN BUATAN CHATGPT TERHADAP MINAT BELAJAR MATA PELAJARAN PPKn PADA PESERTA DIDIK DI SMP NEGERI 1 BOYOLANGU - Tegar Lutfian Budi; M. Abdul Roziq Asrori; Nurna Listya Purnamasari (JIP: Jurnal Ilmu Pendidikan, 2025)
This research aims to determine the influence of using the artificial intelligence application ChatGPT on students' interest in learning Civics (PPKn) at SMP Negeri 1 Boyolangu. The background of the study is the increasing integration of digital technology in education, where students often use AI-based tools to support their learning process. ChatGPT, as a text-based assistant, offers instant responses. However, unmoderated usage may negatively affect students' learning motivation and interest. This study employs a quantitative approach using questionnaires and statistical analysis through simple linear regression. The result shows a significance value of 0.000 with a t-count of 4.784 > t-table of 1.992, indicating a significant influence of ChatGPT usage on learning interest. Educators are encouraged to guide students in utilizing ChatGPT effectively as a supplementary tool rather than a substitute in the learning process.